An An Innovative Approach to Identifying the Location of Myocardial Infarction Using the Einthoven Triangle - chusnul, rachmat; Yasin, Dudella Desnani Firman (Sekolah Tinggi Ilmu Kesehatan YARSI Mataram, 2026)
Introduction. One of the essential competencies for nursing students is the ability to determine the location of myocardial infarction in cases of Acute Coronary Syndrome (ACS). This learning material is considered complex; therefore, specific strategies are needed to help students understand it more easily. The purpose of this study was to determine the effectiveness of the Einthoven triangle illustration in improving nursing students’ ability to identify the location of myocardial infarction. Methods. This study employed a one-group pre-test post-test design with a population of nursing students from the Faculty of Health Sciences, Tribhuwana Tunggadewi University. The study included seventh-semester nursing students with active enrollment who had no prior education or training in infarction localization. A total of 50 respondents were randomly selected. The Einthoven triangle illustration served as the independent variable, and the ability to determine the location of myocardial infarction served as the dependent variable. Data were collected using a test sheet and analyzed using the Wilcoxon test with a significance level of α = 0.05. Results. There was a twofold improvement in students’ ability to identify infarction sites before and after being taught using the Einthoven triangle method (median = 2 vs. 4). The Einthoven triangle illustration was proven effective in enhancing nursing students’ ability to determine the location of myocardial infarction (p = 0.000). Conclusion. To effectively deliver complex learning materials, it is essential to present them in simplified formats—such as diagrams, animated videos, or other visual aids—to facilitate students’ understanding.